Use of Effective Core Potential Calculations for the Conformational and Vibrational Study of Platinum(II) Anticancer Drugs. cis-Diamminedichloroplatinum(II) as a Case Study - Fiuza, Sónia M. (2008)
In the light of the recognized anticancer properties of cisplatin-type inorganic systems, the exact knowledge of their conformational preferences is of the utmost importance for understanding their biological activity. The present study reports the use of theoretical (quantum mechanical) calculations for achieving this goal. An alternative calculation method to the use of the AE basis sets, both accurate and computationally feasible, was presently tested for the conformational and vibrational study of cis-diamminedichloroplatinum(II). Effective core potentials (ECPs) were used, within the HF methodology and, within the B3LYP and mPW1PW DFT protocols. The DFT methods (particularly mPW1PW) were found to be the best choice for describing cDDP (as compared to the HF methodology).